Motivation and context of concurrent stimulant and opioid use among persons who use drugs in the rural United States: a multi-site qualitative inquiry. - Fredericksen, R. J; Baker, R.; Sibley, A.; Estadt, A. T; Colston, D.; Mixson, L. S; Walters, S.; Bresett, J.; Levander, X. A; Leichtling, G.; Davy-Mendez, T.; Powell, M.; Stopka, T. J; Pho, M.; Feinberg, J.; Ezell, J.; Zule, W.; Seal, D.; Cooper, H. L; Whitney, B. M; Delaney, J. A; Crane, H. M; Tsui, J. I (Tufts University. Tisch Library., 2024)
Keywords: Polydrug use, Concurrent stimulant and opioid use, Methamphetamine use, Rural.; Springer Open.